1997
DOI: 10.1007/bf02316805
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis of primary melanoma to two separate lymph node basins: Prognostic significance

Abstract: The survival rate of melanoma patients with regional metastases in two lymph node basins is lower than that of patients with an equal tumor burden confined to a single basin. This suggests that primary melanomas metastasizing to more than one lymph node basin may have a higher metastatic potential, or that dual-basin involvement may increase the risk of systemic spread. We advocate lymphatic mapping, sentinel node biopsy, and selective lymphadenectomy as a cost-effective technique with little morbidity to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…Dale et al 26 found that 5-year survival in patients with dual-basin involvement was lower than that of patients with single-basin involvement (33% vs. 48%; P ϭ .001) in a study of 406 patients undergoing regional lymphadenectomy of two separate lymph node basins. Moreover, by multivariate analysis, the number of basins involved, as well as number of nodes involved, were significant independent prognostic factors for survival.…”
Section: Discussionmentioning
confidence: 95%
“…Dale et al 26 found that 5-year survival in patients with dual-basin involvement was lower than that of patients with single-basin involvement (33% vs. 48%; P ϭ .001) in a study of 406 patients undergoing regional lymphadenectomy of two separate lymph node basins. Moreover, by multivariate analysis, the number of basins involved, as well as number of nodes involved, were significant independent prognostic factors for survival.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, Jiminez et al [ 8 ] found that patients with MLBD had a worse prognosis, independent of SLN status. Dale et al [ 14 ] also showed that overall survival was reduced in patients with dual basin involvement versus single basin involvement (median overall survival of 33 vs 56 months). A further interesting study by Wall et al [ 15 ] found that multiple lymphatic channels to a single basin were an independent risk factor for locoregional recurrence as well as increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Although spread of extremity lesions is often predictable, the use of sentinel lymph node mapping has shown that a high proportion of head, neck, and trunk melanomas drain to unexpected nodal basins or have drainage to two lymph node basins. In addition, patients with disease in two nodal groups have a worse prognosis than those with disease in one nodal group (140). Results of only a single study (141) have suggested that FDG PET has a sensitivity near that of sentinel lymph node mapping, although it has been shown to have a specificity as high as 97% (142,143).…”
Section: Melanomamentioning
confidence: 97%